PENGUATAN LITERASI ZAKAT PRODUKTIF BERBASIS KEARIFAN LOKAL DI KAMPUNG ZAKAT: PENDEKATAN HOLISTIK BER-ISI (INTELEKTUALITAS, SPIRITUALITAS, DAN INTEGRITAS) - Abdul Wasik; Saifullah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The Zakat Village Program is a strategic initiative aimed at community empowerment through the productive management of zakat. This community service activity was conducted in Zakat Village, Sulek Village, Tlogosari Subdistrict, Bondowoso Regency. The objective is to enhance productive zakat literacy based on local wisdom through the Holistic Productive Zakat with ISI Approach, which encompasses three main pillars: Intellectuality, Spirituality, and Integrity. The implementation methods included needs assessment, training, mentoring, and social impact evaluation. The results indicate a significant improvement in the community's understanding of productive zakat, along with the formation of productive business groups rooted in local values. This community service contributes to strengthening a zakat empowerment model that emphasizes the social and spiritual sustainability of society. This article recommends the replication of this model in other regions with appropriate contextual adjustments.